Effects of Video-Guided Digital Menstrual Exercise on Premenstrual Syndrome and Dysmenorrhea Among Adolescent Girls: A Quasi-Experimental Study - Permatasari, Devi; Hamranani, Sri Sat Titi; Alfisyahrina, Zahra; Supardi, Supardi (Journal of Applied Nursing and Health, 2026)
Background: Adolescence is a transitional period of reproductive maturation in which many girls experience premenstrual syndrome and dysmenorrhea that can affect physical, psychological, and academic functioning. Video-guided digital menstrual exercise may help reduce these symptoms through relaxation and improved uterine circulation. However, evidence on nurse-led digital menstrual exercise remains limited; therefore, this study aimed to examine its effects on premenstrual syndrome symptoms and dysmenorrhea intensity among adolescent girls. Methods: This quasi-experimental pretest–posttest control group study followed TREND guidelines. From 237 female students, 70 were selected through purposive sampling and assigned to intervention and control groups. The intervention was video-guided digital menstrual exercise, while outcomes were premenstrual syndrome and dysmenorrhea intensity measured using validated questionnaires and the Numeric Rating Scale (NRS). Data were analyzed using McNemar, Wilcoxon Signed Rank, and Mann–Whitney tests with p < 0.05. Results: The intervention group showed a significant reduction in premenstrual syndrome symptoms, with 74.3% of participants reporting no premenstrual syndrome after the intervention video guided digital menstrual exercise program (p < 0.001). Dysmenorrhea intensity also significantly decreased, as 34.3% of participants reported no pain after the intervention, and a significant difference in pain intensity was observed between the intervention and control groups (p < 0.001). The results of the Mann–Whitney U test showed a statistically significant difference in pain intensity between the intervention and control groups (p < 0.001), with a very large effect size (r = 0.86). Conclusion: Video-guided digital menstrual exercise is effective in reducing premenstrual syndrome symptoms and alleviating dysmenorrhea among adolescent girls with its effects plausibly explained through physiological and neuroendocrine mechanisms. This intervention can be recommended as a safe, practical, and non-pharmacological strategy to be implemented in school health programs to support adolescent reproductive health and improve daily functioning